Negotiating by the light of the law : a report on the effect of law on the negotiation of disputes - Harvey, Matt.; Karras, Maria; Parker, Stephen; Law and Justice Foundation of New South Wales (Annandale, N.S.W. : Federation Press, 2012)
Reports on a project where researchers tested claims made about the relative merits of fixed rules and discretionary principles on negotiation in legal disputes. The researchers selected contrasting norms extracted from family law and contract law for testing, undertook an extensive literature review and created simulation experiments for lawyers.
Keywords: Dispute resolution (Law) -- Australia; Justice, Administration of -- Australia; Negotiation -- Australia